(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Present proposition is an endeavour to characterize contemporary women Indian artist’s mission for remarkable and imaginative style of articulation which hypnotizes the watcher in calculated accounts that they have encountered in their lives and have been transformed into insightful art work. Their art works are intertwined with social strokes deciphering the circumstance of present day. Their perceptions about the neighbourhood and worldwide setting are the sign of the worry and feeling about the general public. These artists built up a pictorial language that articulated their mindfulness and put them as responsive operators of society and constrained them to communicate their fierceness about women related issues as well as about financial difference, impacts of fast urbanization, ecological issues, common pressure, riots and urban bedlam and different social disparities in the public arena.